Evolution of zircon deformation mechanisms in a shear zone (Lanzo massif, Western-Alps) - Kaczmarek, Mary-Alix; Reddy, Steven; Timms, Nicholas Eric (Elsevier BV, 2011)
Magmatic zircons within two sheared gabbroic dykes from the peridotitic massif of Lanzo (Western-Alps, Italy) revealed evolution of deformation from crystal plasticity to rigid body rotation during shear zone evolution. This is the first time that multiple zircon grains have been analysed in a kinematic context in a shear zone. Zircon grains recorded crystal plastic deformation activating the commonly inferred <100>{001} and <001>{100} glide-systems to the newly identified <001>{110} glide-system. The exact selection of glide-system could be dependant of deformation conditions such as pressure, temperature, and strain rate. Moreover, the activation of one or several glide-systems within a single grain could be favoured by the primary orientation of the grains combined with a high strain rate. In these sheared gabbros, the deformation mechanisms evolve from plastic deformation at low strain rate conditions to increase strain, strain softening and localisation of deformation. The progressive shear zone development and the softening of the matrix relative to the zircon has lead to a switch from crystal-plasticity to rigid body rotation of zircon. The zircon grains rigid body rotation involved that their long axes became parallel to the lineation of the shear zone, causing reorientation and dispersion of the misorientation axes away from kinematic Y.